Preparation and Electrochemical Properties of Molybdenum Disulfide Nanomaterials - Pin-Syuan Chen; Yi Hu; Si-Ying Li; Marta Mazurkiewicz-Pawlicka; Artur Małolepszy (Engineering Proceedings, 2025)
As a transition metal chalcogenide, molybdenum disulfide is an important two-dimensional material. Due to its structural anisotropy, its different morphological structures impact performance. Therefore, improving existing preparation methods enhances its applications. Single-layer molybdenum disulfide is a direct bandgap semiconductor with excellent mechanical properties and chemical stability. We chose ammonium molybdate as the molybdenum source and L-cysteine as the sulfur source. By changing the pH and the reaction time in the environment, the hydrothermal method is used to synthesize the precursor and molybdenum disulfide with different morphologies to control its morphology. Electrochemical test results showed that the specific capacity of molybdenum disulfide synthesized at a current density of 0.6 A reaches 187.79 F/g at a reaction time of 24 h and a pH of 0.6. Its microstructure is in the shape of a flower ball, with a single piece size of about 50 nm and a thickness of about 5 nm. Its specific surface area reaches 36.88 m2/g, which provides enough active sites.